Software for kinematic analysis problem solution of manipulators kinematic chains with 3rd and 4th class joints; Технологии Microsoft в теории и практике программирования - Yakovlev A. S. (Автоматизированные системы управления и мехатроника, 2013)
Заглавие с титульного листа.